2017
DOI: 10.5301/hipint.5000538
|View full text |Cite
|
Sign up to set email alerts
|

Infection and failure rates following total hip arthroplasty for septic arthritis: a case-controlled study

Abstract: Two-stage and single-stage THA for active and quiescent native hip infection respectively, achieved similar outcomes to THA for primary osteoarthritis in controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
43
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 22 publications
(48 reference statements)
4
43
0
2
Order By: Relevance
“…The results are the same as in previous studies [25]. In addition, the proportion of heterotopic ossification was 4.95% (5 hips), which was also lower than that reported in previous studies [4, 26], and the proportion of heterotopic ossification in these studies was 28.5% (2 out of 7 hips) and 9.4% (16 out of 170 hips), respectively.…”
Section: Discussionsupporting
confidence: 85%
“…The results are the same as in previous studies [25]. In addition, the proportion of heterotopic ossification was 4.95% (5 hips), which was also lower than that reported in previous studies [4, 26], and the proportion of heterotopic ossification in these studies was 28.5% (2 out of 7 hips) and 9.4% (16 out of 170 hips), respectively.…”
Section: Discussionsupporting
confidence: 85%
“…Recently, the two-stage procedure to a TJA may be considered as a worthy alternative in the management of SA [2, 4, 5]. Papanna et al [2] reported on 18 cases with SA who underwent one-stage or two-stage TJA based on whether the infection was active or quiescent. There was no reinfection or implant failure in this cohort at a mean follow-up of 70 months.…”
Section: Discussionmentioning
confidence: 99%
“…The evolutive septic arthritis (SA) of the hip and knee in adults is a rare but dramatically disastrous disease. Evolutive SA is known to potentially cause devastating cartilage and bone damage as well as poor joint function overall [1, 2]. Recently, the incidence of SA is increasing owing to the aging population and more invasive joint procedures performed [3].…”
Section: Introductionmentioning
confidence: 99%
“…We are aware of only three studies that have explored this topic. One small study [12] compared reinfection and occurrence of PJI in 18 patients who had hip native septic arthritis and were treated with THA using single-(n = 11 patients) and two-stage approaches (n = seven patients) compared with a control cohort of 18 patients who underwent routine primary THA with mean followup of 70 months. They reported no infections in either cohort.…”
Section: Discussionmentioning
confidence: 99%
“…However, a clear link between a history of a resolved native joint septic arthritis as a direct risk factor for PJI when primary TJA is performed in the same joint has not clearly been established. Previous studies have suggested contradictory evidence and have had results that varied between reporting substantially higher PJI rates [14] to very low or no reported PJI rates [2,4,12]. However, most of these studies mainly aimed at reporting on the outcomes of TJA as a treatment option for patients with persistent or quiescent native joint septic arthritis versus investigating previous native joint septic arthritis as an independent risk factor for developing PJI.…”
Section: Introductionmentioning
confidence: 99%